Assessing the impact of national level interventions on workplace respiratory disease in the UK: part 1—changes in workplace exposure legislation and market forces. Issue 7 (17th April 2013) - Stocks, S J; McNamee, R; Turner, S; Carder, M; Agius, R M
Abstract : Objective: The 2004 amendment to the Control of Substances Hazardous to Health 2002 regulations (COSHH 2004) introducing workplace exposure limits (WELs) was enacted in the UK in 2005. This study aimed to determine whether introducing this legislation coincided with a reduction in the incidence of work-related short latency respiratory disease (SLRD) attributed to the agents with a WEL. The second objective was to determine whether changes in legislation, WELs and market forces coincided with a reduction in the incidence of SLRD attributed to glutaraldehyde and latex. Method: Reports of SLRD made to the Surveillance of Work-related and Occupational Respiratory Disease scheme were used to estimate the change in incidence within reporters between two time periods (interrupted time series design) using a longitudinal, negative binomial regression model with β distributed random effects. A statistical interaction term was included in the model to make comparisons between the groups defined by suspected causal agent and/or occupation, essentially comparing two interrupted time series. Time periods were defined prospectively representing the changes in legislation or market forces. Results: The introduction of the COSHH 2004 legislation in the UK coincided with a significant reduction in reports of SLRD attributed to agents with a WEL relative to those without a WEL (ratio of incidence rate ratios: 0.70; 95% CI 0.52 to 0.93) and a significant reduction in SLRD attributed to glutaraldehyde in healthcare workers (0.20; 0.07 to 0.57) and latex in all workers (0.37; 0.16 to 0.85). Conclusions: These data are consistent with a beneficial effect of legislation aiming to reduce workplace exposures.